Profesionalisme Kinerja Aparatur Pemerintah Kecamatan Banjarsari Kota Surakarta (Studi Kasus Profesionalisme Kinerja Aparatur Pemerintah di Kecamatan Banjarsari Kota Surakarta Tahun 2016) - Wardani, Nurul Hanifah Anita; , Dra. Hj. Sri Arfiah, SH, MPd (2016)
This study aims to describe professionalism of performance the government apparatus Subdistrict Banjarsari of Surakarta City include the implementation of the professionalism of performance the government apparatus in Subdistrict Banjarsari of Surakarta City, obstacles encountered, and the solution given. This study used a qualitative research with case study strategy. Data collected by observation, interview, and documentation. Test the validity of the data by triangulation of data sources and data collection techniques. Analysis of the data using interactive analysis techniques through data collection, data reduction, presentation, and conclusion. The results showed that the professionalism of Subdistrict Banjarsari of Surakarta City have been implemented with good efficiency and effectiveness by government apparatus in Subdsitrict Banjarsari of Surakarta City to realize the goals and purpose government of Subdistrict Banjarsari of Surakarta City. The solution that has been done is to promote coaching for the government apparatus Subdistrict Banjarsari of Surakarta City to create the effectiveness and efficiency according to the functions of government; goals; purpose; and the development of the Subdistrict Banjarsari of Surakarta City, and optimize the job and the quality of work according to ability and the knowledge their respective for government apparatus in Subdistrict Banjarsari of Surakarta City.